Transcriptome and proteome depth analysis indicate ABA, MAPK cascade and Ca2+ signaling co-regulate cold tolerance in Rhododendron chrysanthum Pall. - Zhang, Qingyi; Li, Yue; Cao, Kun; Xu, Hongwei; Zhou, Xiaofu (Frontiers in Plant Science, 2023)
Cold stress is a global common problem that significantly limits plant development and geographical distribution. Plants respond to low temperature stress by evolving interrelated regulatory pathways to respond and adapt to their environment in a timely manner. Rhodoendron chrysanthum Pall. (R.chrysanthum) is a perennial evergreen dwarf shrub used for adornment and medicine that thrives in the Changbai Mountains at high elevations and subfreezing conditions. In this study, a comprehensive investigation of cold tolerance in R.chrysanthum leaves under cold using physiological combined with transcriptomic and proteomic approaches. There were 12,261 differentially expressed genes (DEGs) and 360 differentially expressed proteins (DEPs) in the low temperature (LT) and normal treatment (Control). Integrated transcriptomic and proteomic analyses showed that MAPK cascade, ABA biosynthesis and signaling, plant-pathogen interaction, linoleic acid metabolism and glycerophospholipid metabolism were significantly enriched in response to cold stress of R.chrysanthum leaves. We analyzed the involvement of ABA biosynthesis and signaling, MAPK cascade, and Ca2+ signaling, that may jointly respond to stomatal closure, chlorophyll degradation, and ROS homeostasis under low temperature stress. These results propose an integrated regulatory network of ABA, MAPK cascade and Ca2+ signaling comodulating the cold stress in R.chrysanthum, which will provide some insights to elucidate the molecular mechanisms of cold tolerance in plants.